Measuring tax burden efficiency in OECD countries : an International Comparison - Afonso, António (2024)
In this paper, we estimate the potential tax burden in a panel data set comprising OECD countries over the period 2000-2021. To this end, we use non-parametric and parametric techniques: Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA). In this way, it will be possible for us to identify which countries are close to their potential tax capacity and which are far from it. Moreover, we can determine whether they may sustain an increase (decrease) in their actual tax burden depending on whether the tax effort ratio is lower or higher relatively to other similar countries in the sample. Non-parametric and parametric results coincide rather closely on the positioning of the countries vis-à-vis the production possibility frontier and on their relative distances to the frontier. Efficient countries most of the times are: Belgium, Colombia, Finland, France, Italy, Latvia, Slovak Republic, and Sweden.